Mechanical properties and cell-culture characteristics of a polycaprolactone kagome-structure scaffold fabricated by a precision extruding deposition system. (13th September 2017) - Lee, Se-Hwan; Cho, Yong Sang; Hong, Myoung Wha; Lee, Bu-Kyu; Park, Yongdoo; Park, Sang-Hyug; Kim, Young Yul; Cho, Young-Sam
Abstract: To enhance the mechanical properties of three-dimensional (3D) scaffolds used for bone regeneration in tissue engineering, many researchers have studied their structure and chemistry. In the structural engineering field, the kagome structure has been known to have an excellent relative strength. In this study, to enhance the mechanical properties of a synthetic polymer scaffold used for tissue engineering, we applied the 3D kagome structure to a porous scaffold for bone regeneration. Prior to fabricating the biocompatible-polymer scaffold, the ideal kagome structure, which was manufactured by a 3D printer of the digital light processing type, was compared with a grid-structure, which was used as the control group, using a compressive experiment. A polycaprolactone (PCL) kagome-structure scaffold was successfully fabricated by additive manufacturing using a 3D printer with a precision extruding deposition head. To assess the physical characteristics of the fabricated PCL–kagome-structure scaffold, we analyzed its porosity, pore size, morphological structure, surface roughness, compressive stiffness, and mechanical bending properties. The results showed that, the mechanical properties of proposed kagome-structure scaffold were superior to those of a grid-structure scaffold. Moreover, Sarcoma osteogenic (Saos-2) cells were used to evaluate the characteristics of in vitro cell proliferation. We carried out cell counting kit-8 (CCK-8) and DNA contents assays. Consequently, the cell proliferation of the kagome-structure scaffold was increased; this could be because the surface roughness of the kagome-structure scaffold enhances initial cell attachment.